Sclerosing angiomatoid nodular transformation of the spleen in a patient with Maffucci syndrome: a case report and review of literature - Xiao-Dan Huang; Hao-Sen Jiao; Zheng Yang; Chuang-Qi Chen; Yu-Long He; Xin-Hua Zhang (BMC, 2017)
Abstract Background Maffucci syndrome is a congenital, non-hereditary mesodermal dysplasia characterized by multiple enchondromas and hemangiomas. The presence of visceral vascular lesions in this syndrome is exceedingly rare. Case presentation We report a 26-year-old female who was diagnosed with Maffucci syndrome along with sclerosing angiomatoid nodular transformation (SANT) of the spleen. The patient underwent a laparoscopic splenectomy. Immunostaining of the excised specimen revealed 3 distinct types of vessels in the angiomatoid nodules: CD34−/CD8−/CD31+ small veins, CD34−/CD8+/CD31+ sinusoids, and CD34+/CD8−/CD31+ capillaries, leading to the diagnosis of SANT of the spleen. Conclusions This case reports the first patient in the literature exhibiting the features of Maffucci syndrome along with SANT of the spleen. The spleen is probably a predilection site of visceral vascular lesions in this syndrome with a proportion of 4 out of 14. An abdominal Computed Tomography (CT) scan is recommended for any cases of abdominal discomfort. Surgical excision is usually sufficient because of the relatively benign behavior of SANT, however, a more aggressive follow-up is proposed due to the high risk of malignant transformation of enchondromas and development of other neoplasms associated with this syndrome. Further studies are required to reveal its genetic basis for comprehensive prognosis evaluation and therapeutic guidance.